The Idea Methods of Introducing Performance - Based Budgets in the Public Finance Sector in Poland - Lange, Urszula (Studia Oeconomica Posnaniensia, 2013)
The objective of this study is to present the idea of performance-based budgeting in public spending. There is no doubt that the implementation of taskoriented budgeting into Polish public finances is a new concept which raises a number of questions and concerns. Task-oriented budgeting is only mandatory for the state budget, but its implementation in local government units is optional. In this paper a comparison is made between budgets done in the traditional way and performance- based budgets. It also presents possible approaches for the implementation of performance-based budgeting in local government units. The paper does not include any results of empirical research, it is for illustrative purposes only. It is based on current legislation and the available literature.